Vanuatu : Technical Assistance Report-Feasibility Study on the Introduction of Quarterly National Accounts. (IMF Staff Country Reports; Country Report ;, 2021)
The Vanuatu National Statistics Office (VNSO) requested a mission by the IMF's Pacific Financial Technical Assistance Centre (PFTAC) for conducting a feasibility study on the implementation of a quarterly national accounts (QNA) in Vanuatu. This study outlines the staff, organizational and data requirements for Vanuatu to implement a quarterly national accounts program.